Discourse on Artificial Intelligence Design Using ITS and SDLC Methods in Building Islamic Religious Education Learning Applications - Syahrizal, Syahrizal; Yasmi, Fifi; Mary, Thomson (Journal of Pragmatics and Discourse Research, 2023)
The development of increasingly sophisticated programming language technology where designed algorithms are able to think intelligently have been used for various purposes that are good for humans. This technology can also be applied to Islamic religious learning by using an intelligent tutoring system combined with artificial intelligence to: find sources of books, source modules, hadiths, verses of the Koran and their translations that are really related to learning with correct and solid data and compare Islamic teaching methods. The application program was built using two methods, namely the system design method System Development Life Cycle and the Intelligent Tutoring System method. The System Development Life Cycle method is used to build a comprehensive system that includes design tools such as use cases, activities, classes, sequences. While the Intelligent Tutoring System method is used in designing intelligent algorithms with a programming language as a machine to operate this learning Artificial Intelligence system. The result of this study is a smart application program for Islamic religious learning and is applied in high schools in the province of West Sumatra, Indonesia with an application effectiveness level of up to 96% with an error rate index of 0.23.